STUDI KUANTITAS DAN KUALITAS MATA AIR KOBARI JAYA SEBAGAI SUMBER AIR BAKU DI KABUPATEN SUPIORI PROVINSI PAPUA - Jacson Victor Morin; Darma Santi (FMIPA Universitas Papua, 2020)
A study on the quantity and quality of the Kobari Jaya spring in Supiori Regency has been conducted. Research on the quality test of Kobari Jaya springs has never been conducted. This study uses descriptive methods and laboratory tests and uses a comparative method of test results against the quality standard value based on PERMENKES No. 492 Tahun 2010 tentang Persyaratan Air Minum. The test results show that the average meets quality standards. The instruments used to test water samples include AAS and UVVis spectrophotometer. Several parameters such as pH, COD, BOD, DO, Phosphate, Fecal Coliform and Total Coliform exceed the predetermined quality standard values. The cause of this high parameter occurs naturally. The test results concluded that the Kobari Jaya spring is very suitable to be used as a source of raw water supply in the Kobari Jaya area in particular and the Supiori area in general